Gaya Hidup Hedonisme Mahasiswa Pascasarjana di Media Sosial - Elia Firda Mufidah; Peppy Sisca Dwi Wulansari (JKI (Jurnal Konseling Indonesia), 2018)
Graduate students are in early adulthood at the age of 18 to 40 years. As adolescence moves intoadulthood, adulthood (emerging adulthood) is marked by experimentation and exploration. Hedonlifestyle can not be separated from the world of students. Students tend to have a hedon lifestyle inorder not to be labeled obsolete or old age kids. This research uses qualitative research with casestudy type with research subject of guidance and counseling students of State University of Malangclass of 2016. The conclusion shows that graduate student has a hedonism lifestyle is done to getpleasure so that encourage them to complete their duty.